2017
DOI: 10.1016/j.spinee.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Escherichia coli -derived recombinant human bone morphogenetic protein-2 in posterolateral lumbar fusion: an open, active-controlled, randomized, multicenter trial

Abstract: The fusion rate of E.BMP-2 was comparable with that of AIBG following PLF. Good clinical efficacy and safety of E.BMP-2 in spinal fusion were also revealed. It was also suggested that HA shows suitability as a carrier for E.BMP-2. Thus, E.BMP-2 with an HA carrier can be an alternative bone graft material in spinal fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 49 publications
(53 reference statements)
1
38
2
Order By: Relevance
“…However, to date, it is also acknowledged that BMP-2 remains a powerful activator of bone repair, whose delivery needs to be further optimized. Alternative sources of BMP-2 combined with ceramics are emerging, such as those produced in CHO-cells [74] or in E-coli [75, 76].…”
Section: Bone Graft Substitutes Combined With Active Biomoleculesmentioning
confidence: 99%
“…However, to date, it is also acknowledged that BMP-2 remains a powerful activator of bone repair, whose delivery needs to be further optimized. Alternative sources of BMP-2 combined with ceramics are emerging, such as those produced in CHO-cells [74] or in E-coli [75, 76].…”
Section: Bone Graft Substitutes Combined With Active Biomoleculesmentioning
confidence: 99%
“…At the cellular level, it can trigger a healing cascade, induce MSCs to differentiate into osteoblasts or chondroblasts, and promote osteoblast proliferation [ 295 , 296 ]. Accordingly, it has been frequently incorporated into scaffolds for applications ranging from spinal fusion [ 297 , 298 ] to dental and craniofacial regeneration [ [299] , [300] , [301] ]. However, a few studies have found that the direct delivery of cytokines to bone defects could cause individual differences in repair effects.…”
Section: Bioactive Molecular Delivery Based On Bone-healing Mechanismmentioning
confidence: 99%
“…Using genetic recombination with E. coli , much larger amounts of rhBMP-2 can be produced at low cost; however, E. coli -derived rhBMP-2 is not glycosylated and shows reduced biological activity [18]. Nonetheless, recent pre-clinical and clinical studies using E. coli -derived rhBMP-2 have shown successful results in bone regeneration in orthopedic and bone augmentation procedures in dentistry [19,20,21].…”
Section: Rhbmp-2 Delivery In Protein Formmentioning
confidence: 99%